2014
DOI: 10.1111/asj.12333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypothalamic dopamine on growth hormone‐releasing hormone‐induced growth hormone secretion and thyrotropin‐releasing hormone‐induced prolactin secretion in goats

Abstract: The aim of the present study was to clarify the effects of hypothalamic dopamine (DA) on the secretion of growth hormone (GH) in goats. The GH-releasing response to an intravenous (i.v.) injection of GH-releasing hormone (GHRH, 0.25 μg/kg body weight (BW)) was examined after treatments to augment central DA using carbidopa (carbi, 1 mg/kg BW) and L-dopa (1 mg/kg BW) in male and female goats under a 16-h photoperiod (16 h light, 8 h dark) condition. GHRH significantly and rapidly stimulated the release of GH af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…It was preassumed that a low dosage of dopamine was adequately effective to boost a higher growth. According to Jin and Hashizume (2014), dopamine is involved in growth hormone and prolactin regulation mechanism in goat. Dopamine restrained the somatostatin hormone in hypothalamus, thus the growth hormone releasing hormone (GHRH) was able to be stimulated to secrete growth hormone.…”
Section: Discussionmentioning
confidence: 99%
“…It was preassumed that a low dosage of dopamine was adequately effective to boost a higher growth. According to Jin and Hashizume (2014), dopamine is involved in growth hormone and prolactin regulation mechanism in goat. Dopamine restrained the somatostatin hormone in hypothalamus, thus the growth hormone releasing hormone (GHRH) was able to be stimulated to secrete growth hormone.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Prolactin secretion is stimulated by thyrotropin releasing a hormone (TRH) and inhibited by dopamine. [ 3 ] Moreover, extra-pituitary prolactin found in the cerebral cortex, amygdala, myometrium, lacrimal glands, thymus, immune cell, skin fibroblast, sweat gland, and spinal cord this extra-pituitary prolactin is not regulated by dopamine but through independent factors. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…DOM is a DA D 2 receptor antagonist (Yen ) that does not cross the BBB (Laduron & Leysen ; Delitala et al ); therefore, the hormonal changes observed could be mediated through the pituitary and median eminence. The secretion of PRL is also stimulated by thyrotropin‐releasing hormone (TRH) (Yen ; Hashizume et al , , , ; Sawada et al ; Yaegashi et al ; Jin & Hashizume ). TRH acts directly on the pituitary lactotrophs to secrete PRL (Yen ).…”
Section: Introductionmentioning
confidence: 99%